2013
DOI: 10.1111/dom.12088
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ranging study with the glucokinase activator AZD1656 in patients with type 2 diabetes mellitus on metformin

Abstract: Addition of AZD1656 (individually titrated) to metformin gave significant improvements in glycaemic control up to 4 months, although efficacy diminished over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 25 publications
(42 reference statements)
6
105
0
6
Order By: Relevance
“…However, given the metabolic heterogeneity of ␤-cells in rodent islets (37), the present study suggests that GKAs may be beneficial in poorly responsive ␤-cells while being simultaneously toxic to middle-and highly-responsive ␤-cells through a variety of mechanisms proposed to contribute to glucotoxicity (1). If such "glucotoxic-like" effects of long-term GKA treatment at intermediate glucose concentration were confirmed in human islets, it could contribute to the secondary failure of GKAs in T2D (22,31,47).…”
Section: E636mentioning
confidence: 68%
See 2 more Smart Citations
“…However, given the metabolic heterogeneity of ␤-cells in rodent islets (37), the present study suggests that GKAs may be beneficial in poorly responsive ␤-cells while being simultaneously toxic to middle-and highly-responsive ␤-cells through a variety of mechanisms proposed to contribute to glucotoxicity (1). If such "glucotoxic-like" effects of long-term GKA treatment at intermediate glucose concentration were confirmed in human islets, it could contribute to the secondary failure of GKAs in T2D (22,31,47).…”
Section: E636mentioning
confidence: 68%
“…If GKAs undoubtedly trigger liver steatosis (4,6,34), their potential toxicity to ␤-cells remains unclear (4,35,38,43,44,46). Thus, although some GKAs proved beneficial to ␤-cell survival and GSIS under glucotoxic conditions and in islets from T2D patients (8,35,46), their secondary failure during long-term treatment (22,31,47) reopened the question of their toxicity to ␤-cells. This possible caveat of GKAs has been previously considered nonrelevant on the ground that ␤-cell stimulation is reduced following the GKA-mediated reduction in glycemia (12).…”
Section: E636mentioning
confidence: 99%
See 1 more Smart Citation
“…Although many classes of drugs are currently available for glycemic control in T2DM, there remains a great need for drugs with new mechanisms of action that can be added to or replace currently available drugs (Mittermayer et al, 2015). reduction in hemoglobin A1c (HbA1c) in T2DM patients (Meininger et al, 2011;Wilding et al, 2013;Kiyosue et al, 2013;Kazierad et al, 2013). However, clinical trials of several GK activators also revealed a loss of efficacy over time with sustained treatment and an increase in plasma triglyceride (TG) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Given its major role in glucose metabolism, efforts have been undertaken to develop glucokinase activators as a potential new class of glucose-lowering drugs (4). Clinical studies have demonstrated that these systemic activators are capable of lowering plasma glucose levels, albeit at the expense of hypoglycemia (5,6). This undesired side effect could be circumvented by organ-specific glucokinase activators, which only act in the liver, not in the pancreas (7).…”
mentioning
confidence: 99%